Dietary supplements for athletes in terms of anti-doping regulations - Daria Siodłak; Katarzyna Pokajewicz; Paweł Biernat; Karolina Kulik-Kupka; Katarzyna Jaros; Radosław Jerzy Balwierz (Śląski Uniwersytet Medyczny w Katowicach, 2022)
The motivation to use dietary supplements in sports is very high and strongly correlated with the need to perform better and achieve improved results. Data from the Public Opinion Research Center indicate that nine out of ten Polish adults use supplements, while athletes often use several supplements concomitantly. The usage of supplements depends primarily on the type of sports discipline and increases with the intensity of training and the age of the respondents. The published data also suggests that athletes are willing to take supplements without gathering reliable information about the active substances they contain. Therefore, there are many documented cases of doping, including unintentional doping, in the history of sport. In the case of professional athletes, a significant problem is the risk of the contamination of supplements with substances from the World Anti-Doping Agency (WADA) list. Therefore, one should ensure that the possible benefits of using supplements outweigh the risks of using them. Evaluation of the current diet should be the first step in selecting potential supplementation. This process should be carried out based on an assessment of anthropometric, biochemical, clinical and environmental data. The decision should be based on a complex analysis of the athlete. The analysis presented here is based on the reports of the WADA and scientific literature and it aims to provide information on the use of supplementation in sports, including data on legal regulations and potential risks associated with their use.